[OA164] Vandetanib may act as a radiosensitiser for 177Lu-octreotate treatment of medullary thyroid cancer. (August 2018) - Sandblom, Viktor; Spetz, Johan; Shubbar, Emman; Ståhl, Ingun; Swanpalmer, John; Forssell-Aronsson, Eva
Abstract : Purpose: Medullary thyroid cancer (MTC) is a very rare type of cancer. Most patients diagnosed with MTC present with metastatic disease. Therefore, surgical resection is often complemented by external beam radiotherapy (EBRT) or the use of tyrosine kinase inhibitors. In order to reach distant metastases, systemic therapy is needed. Vandetanib is a tyrosine kinase inhibitor that was recently approved for single-agent treatment of MTC by the U.S. Food and Drug Administration (FDA). Additionally, since many MTC overexpress somatostatin receptors, radiolabelled somatostatin analogues ( e . g . 177 Lu -octreotate) offer a promising treatment option for patients with MTC. The aim of this study was to investigate the potential synergistic effect of combining irradiation and vandetanib for treatment of MTC. Methods: BALB/c nude mice were transplanted with patient-derived MTC cells (GOT2) and treated with EBRT alone, vandetanib alone or a combination of both. The tumour volume was followed and compared with that in untreated GOT2 mice. The radiation dose and the amount of vandetanib were chosen to give moderate effect as single treatment to enable detection of any additive or synergistic effects. Results: We found that the largest reduction in tumour size over time was seen for the animals receiving a combination of both EBRT and vandetanib. Given as single-agent treatment, EBRT and vandetanib resulted in a reduction in tumour size or in tumour growth arrest. For example, at two weeks after start of treatment, the tumour volume was reduced by 64%, 52%, and 73% compared with the untreated control group, for the animals treated with single EBRT, single vandetanib, and the combination, respectively. Conclusions: The results indicate that an additive or even synergistic effect could be achieved when combining irradiation with vandetanib for treatment of patients with MTC. Further studies should be made evaluating the full potential of combining vandetanib with 177 Lu-octreotate for treatment of MTC.